Bilderfronten Die Visualisierung der sowjetischen Intervention in Afghanistan 1979-1989 - Mirschel, Markus (Böhlau, 2019)
The goal of the USSR: an Afghan stability. The result: a Soviet instability. When the Soviet Union moved soldiers to Afghanistan in 1979, it was secretly done - there were no official pictures. The military newspaper Krasnaya Zvezda and the central organ Pravda acted in the early 1980s as a partner in the spirit. The USSR as a peace force was also visually helping the comrades in Kabul. When the last Soviet soldiers left the country in the Hindu Kush in 1989, the event was the focus of the media public. What happened? The externally conducted conflict on Afghan soil had developed into an internal Soviet debate on media interpretive sovereignty, social responsibility and dealing with events.
Description based on print version record.
KU Open Services
Keywords: History / Middle East; History / Russia & The Former Soviet Union; History; Electronic books